2016
DOI: 10.1016/j.msec.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Delivery system for mefenamic acid based on the nanocarrier layered double hydroxide: Physicochemical characterization and evaluation of anti-inflammatory and antinociceptive potential

Abstract: This work shows the increase of the anti-inflammatory and antinociceptive potential of the drug confined into the LDH, as well as, its hemolytic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 40 publications
(44 reference statements)
0
21
0
1
Order By: Relevance
“…Our group has been studying experimental parameters for the intercalation of drugs such as pravastatin and sulindac into LDHs and applying structural, spectroscopic, textural, and thermal techniques for their detailed characterization . We recently reported the biological properties of a LDHs intercalated with the anion of mefenamic acid evaluated through the in vitro cytotoxicity tests by hemolysis, and in vivo tests concerning the anti‐inflammatory activity and nociceptive effect of the intercalated and nonintercalated drug . The mefenamate confinement in the LDH structure decreased its hemolytic effect and potentiated its anti‐inflammatory and analgesic effects.…”
Section: Introductionmentioning
confidence: 64%
“…Our group has been studying experimental parameters for the intercalation of drugs such as pravastatin and sulindac into LDHs and applying structural, spectroscopic, textural, and thermal techniques for their detailed characterization . We recently reported the biological properties of a LDHs intercalated with the anion of mefenamic acid evaluated through the in vitro cytotoxicity tests by hemolysis, and in vivo tests concerning the anti‐inflammatory activity and nociceptive effect of the intercalated and nonintercalated drug . The mefenamate confinement in the LDH structure decreased its hemolytic effect and potentiated its anti‐inflammatory and analgesic effects.…”
Section: Introductionmentioning
confidence: 64%
“…The basal spacing of (003) reflection in blank LDH (Figure 3a) was 8.8 Å calculated by (00l) reflection, which could be attributed to the NO 3 -guests in the interlayer region. 36 When PRN is being intercalated, as shown in Figure 3b, the (003) basal reflection shifted to lower 2θ angle from 10° to 7°, corresponding to an increase of the interlayer distance from 8.8 Å to 12.7 Å. This result indicated that PRN was intercalated into the galleries of LDH.…”
Section: Xrdmentioning
confidence: 88%
“…It is worth to emphasize that the LDHs in the form of chloride were chosen since they are frequently taken as precursors for the preparation of LDH intercalated with drugs by ion exchange method. When using co-precipitation method for LDH–drug synthesis, metal cations in the form of chloride salts are used as reagents and Cl − can be co-intercalated with drugs, as observed for pravastatin and mefenamate LDH carrier 16 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The biocompatibility of LDH has been explored by in vitro tests such as cell viability tests 12 13 , lactate dehydrogenase leakage assay 12 13 14 15 , inflammatory mediators analysis 12 , hemolysis assay 15 16 17 , thrombosis assay 17 , lipid peroxidation 18 , reactive oxygen species (ROS) generation 12 14 and apoptosis 12 14 . On the other hand, the in vivo biocompatibility and the therapeutic potential of LDH particles have been investigated by a minor number of assays through the analysis of biodistribution and accumulation in tissues 18 19 20 21 , stomach lesions 22 , therapeutic effects as anti-tumor 23 and anti-inflammatory activities 16 . Latterly, interesting reports have explored the usage of LDH as a grout material in bone cement for implant in tibia 24 , and as a coating to middle ear prostheses 25 .…”
mentioning
confidence: 99%